Client-facing Interprofessional Project Teams: The Role of Engineers' 'Situated Judgment'. Issue 3 (2nd September 2021) - Wilde, Rachel J.; Guile, David
Abstract : This paper addresses the type of engineering practice associated with 'client-focused interprofessional project teams' C-fIPPTs which is a typical pattern of work associated with engineering consulting companies. To do so, the article introduces the concepts of 'situated judgment' and 'immaterial activity' to the Engineering Studies community. It uses these concepts to demonstrate how engineers with different specialisms, working alongside architects, interior designers, etc., resolve competing conceptions of value among members to enable teams to accomplish project-specific issues. The article makes the above argument by drawing on observational data, interviews and field notes to illustrate the immaterial dimension (i.e. converting non-costed ideas into solutions to problems) of such situated judgments. The article concludes by firstly, explaining how the argument it advances about the distinctive features of engineering work contributes to a broadening of research on engineers work practice and, in doing so, the contribution that engineering studies can make to the field of workplace learning. Secondly, the article highlights the implications of its argument for engineering education and workplace learning.